The Impact of PTPRK and ROS1 Polymorphisms on the Preeclampsia Risk in Han Chinese Women - Huihui Li; Xingyu Yan; Man Yang; Mei Liu; Shan Tian; Mengru Yu; Wei-Ping Li; Cong Zhang (International Journal of Hypertension)
Objective. Preeclampsia (PE) is a severe complication in pregnancy and a leading cause of maternal and infant mortality. However, the exact underlying etiology of PE remains unknown. Emerging evidence indicates that the cause of PE is associated with genetic factors. Therefore, the aim of this study is to identify susceptibility genes to PE. Materials and Methods. Human Exome BeadChip assays were conducted using 370 cases and 482 controls and 21 loci were discovered. A further independent set of 958 cases and 1007 controls were recruited for genotyping to determine whether the genes of interest ROS1 and PTPRK are associated with PE. Immunohistochemistry was used for localization. Both qPCR and Western blotting were utilized to investigate the levels of PTPRK in placentas of 20 PE and 20 normal pregnancies. Results. The allele frequency of PTPRK rs3190930 differed significantly between PE and controls and was particularly significant in severe PE subgroup and early-onset PE subgroup. PTPRK is primarily localized in placental trophoblast cells. The mRNA and protein levels of PTPRK in PE were significantly higher than those in controls. Conclusion. These results suggest that PTPRK appears to be a previously unrecognized susceptibility gene for PE in Han Chinese women, and its expression is also associated with PE, while ROS1 rs9489124 has no apparent correlation with PE risk.